In situ demonstration of Epstein-Barr virus in intravenous drug abusers with generalized lymphadenopathy. Issue 803 (September 1992) - Mampaso, F.; Bellas, C.; Molina, A.; Quereda, C.; Bricio, T.; Buzon, L.
Abstract : We have studied by the in situ hybridization method the presence of Epstein-Barr virus (EBV) DNA genome in lymph node tissues from 11 patients with persistent generalized lymphadenopathy. Using a biotinylated EBV DNA probe, we demonstrated EBV nucleic acid in scattered germinal centre cells in eight of the 11 cases. Our results suggest that EBV is not a determinant factor in the pathogenesis of this lymphadenopathy, but support its possible implication in B cell malignant transformation in cases of AIDS-associated lymphoma.